Child labour a public health perspective - Fassa, Anaclaudia G.; Parker, David L. (David Lewis), 1951-; Scanlon, Thomas J., Dr. (Oxford : Oxford University Press, 2010)
This book discusses issues of child labour such as poverty malnutrition, social disadvantage, gender, globalisation, and education, and looks at both physical and psychological threats. The editors concentrate on child labour in the developing world where most of it occurs.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child labor -- Developing countries; Child labor -- Developing countries -- Case studies; Child labor -- Health aspects -- Developing countries; Child labor -- Health aspects -- Developed countries -- Case studies